Faktor Pemicu Kecemasan Siswa dalam Melakukan Pembelajaran Daring di Masa Pandemi Covid-19 - Dwi Hardani Oktawirawan (Universitas Batanghari Jambi, 2020)
Students in Indonesia conduct online learning from home in an effort to socially distancing during the covid-19 pandemic. The purpose of this study is to determine the triggers of anxiety experienced by students and the efforts made to overcome these anxieties. This study involved 74 informants who were high school students in Indonesia. Informants were asked to fill in open questions related to research topics through online forms. The results showed that the triggers for students' anxiety during online learning are difficulty understanding the material, difficulty working on assignments, the availability and condition of the internet network, technical obstacles, and concerns about subsequent assignments. The efforts made to overcome these anxieties are self-study, immediate work on assignments, discussion with teachers and friends, praying, self-encouraging, and doing other activities such as watching movies, listening to music, playing games, sleeping, eating, and doing sports.